Proteomic analysis reveals phage-driven metabolic shifts and biofilm disruption in methicillin-resistant Staphylococcus aureus (MRSA) - Dakheel, Khulood Hamid; Rahim, Raha Abdul; Al-Obaidi, Jameel R.; Razali, Nurhanani; Neela, Vasantha Kumari; Hun, Tan Geok; Yusoff, Khatijah (Springer Science and Business Media B.V., 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) biofilms pose a severe risk to public health, showing resistance to standard antibiotics, which drives the need for novel antibacterial strategies. Bacteriophages have emerged as potential agents against biofilms, especially through their phage-encoded enzymes that disrupt the biofilm matrix, enhancing bacterial susceptibility. In this study, two bacteriophages, UPMK_1 and UPMK_2, were propagated on MRSA strains t127/4 and t223/20, respectively. Biofilms formed by these strains were treated with phages at specified concentrations, followed by protein extraction and analysis. Comparative proteomic profiling was performed using one-dimensional and two-dimensional SDS-PAGE, with protein identification facilitated by MALDI-TOF/TOF MS spectrometry, to observe biofilm degradation effects. Proteomic analysis revealed that phage treatment induced significant changes in biofilm protein expression, particularly with upregulated ribosome-recycling factors and elongation factors linked to enhanced protein synthesis, reflecting a reactivation of amino acid metabolism in the treated biofilms. This was marked by upregulated intracellular proteases like CIpL, which play a role in protein refolding and degradation, critical for phage progeny production and biofilm disruption. Phage treatment demonstrated notable effects on the metabolic and protein synthesis pathways within MRSA biofilms, suggesting that phages can redirect bacterial cellular processes to favour biofilm breakdown. This indicates the potential of bacteriophages as a viable adjunct to traditional antimicrobial approaches, particularly in combating antibiotic-resistant infections like MRSA. The study underscores the efficacy of bacteriophages as anti-biofilm agents, offering a promising strategy to weaken biofilms and combat antibiotic resistance through targeted disruption of bacterial metabolic pathways and biofilm integrity.